Pemanfaatan Fasilitas Dan Sumber Belajar Dalam Implementasi Kurikulum 2013 Di SMP Negeri 1 Sawit Boyolali Semester Genap Tahun Ajaran 2014/2015 - Ningsih, Rakhmi, Dra. Hariyatmi, M.Si (2015)
One of the keys to success in the implementation of the curriculum 2013 is the utiliztion of facilities and learning resources optimally. This study aims to determine how the utilization of facilities and learning resources at Sawit of 1 junior high school Boyolali academic year 2014/2015. This type of research is qualitative descriptive with sample grade science teacher at VII and VIII. Technique data collecting RPP documentation techniques for the utilization of facilities and learning resources, observation of learning to utilization the facilities and learning resources and interview (optional). Results of research on the preparation of the RPP indicates that a science teacher in the selection and use of instructional media 100%, the utilization of variation of instructional media 81.25%, utilize media use and optimally 74.99%, utilizing the media for scientific learning 89.58%. In the aspect of learning resource usage of books 79.72%, web address 62.5%, LKS 100%, utilization of school areas 22.91%, the media as a learning resource 83.3%. The result of observation at learning activity of learning for classroom space utilization 93.75%, utilize laboratory 67.85%, libraries 92.85%. In the aspect of learning resources utilizing skills learning resource 74.99%, involving students 66.65% and generate attractive message 100%. It can be concluded that the utilization of learning facilities excellent category (78.84%) and the use of learning resources both categories (73.93%) in the preparation of lesson plans (RPP) and utilization of learning facilities either category (94.44%) and the use of learning resources both categories (74.47%) on the implementation of learning Keywords: learning facilities, learning resources, implementation curriculum 2013